Max E. G. Bartels and the Javan Lapwing Vanellus macropterus - Collar, N J; Schariemann, J P. W; Fisher, C T (KUKILA, 2000)
The Javan Lapwing Vanellus macropterus was (and just possibly still is) a bird species endemic to Java, although there is debatable nineteenth century evidence of its occurrence on Sumatra. It has not been seen since 1940, and indeed almost nothing has ever been published on the species (the scant details are assembled in BirdLife Internafional's Threatened birds of Asia, in prep.). However, the Swiss German plantation owner Max E. G. Bartels (1871 1936; see Stresemann 1937, Rozendaal 1981) kept extensive manuscript and typescript notes on Javan birds, which he clearly intended to publish at one stage. These are held at the National Museum of Natural History Naturalis, Leiden, Netherlands. The notes contain an invaluable summary of Bartels's experience of the Javan Lapwing. This material has been selected, condensed and reworked into the entry on the species in Threatened birds of Asia, but because it is a unique record (and because there are items of information which do not concern conservation and were therefore not used in BirdLife's account), we felt it would be worthwhile reproducing the entries in its entirety in the interests of science and posterity. The translation, from German, is ours.